Prevalência de disfagia orofaríngea no acidente vascular cerebral após cirurgia cardíaca - Almeida, Tatiana Magalhães De (2015)
Abstract:PURPOSE: to determine the prevalence of oropharyngeal dysphagia in patients undergoing cardiac surgery and who developed stroke in a public referral hospital.METHODS: a retrospective descriptive clinical cross-sectional study conducted by collecting data on clinical assessment protocols of oropharyngeal swallowing in the period November 2010 to November 2011, including the protocols of 25 individuals for clinical evaluation of oropharyngeal dysphagia with post-operative stroke during the study period who were assisted by the Speech-Language Pathology team. Clinical swallowing assessment was based on clinical tools and swallowing classified as normal, mild, moderate and severe dysphagia.RESULTS: of the twenty-five (100%) patients, 24 (96%) presented dysphagia in clinical evaluation and 1 (4%) did not (95% [IC]: 79.6- 99.9). It was found that 41.66% had severe dysphagia, 33.66% moderate and 25% mild dysphagia.CONCLUSION: there was a high prevalence of oropharyngeal dysphagia in patients with stroke after cardiac surgery.